THE INTEGRAL CHARACTERISTICS OF AN INDUCTION LOOP PLACED ABOVE MULTI-LAYERED CONDUCTIVE SEMISPACE - REVA, M.; RUDENKO, T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
The paper presents a completed solvation for the task about integral characteristics of an induction loop situated above a layeredconductive half-space.The principal development sets up relation betveen multilaers electric section parameters and integral characteristics of an induction loop feeded with harmonic current. This is to provide theoretical ground for a new elektromagnetic exploration technique, being named integral induction sounding.